PENGEMBANGAN KONSERVASI BUDAYA KESENIAN TRADISIONAL TEMBANG JAWA DI SEKOLAH - Kismini, Elly (Forum Ilmu Sosial, 2012)
Conservation of cultural artistic development can be done through local content Java language lessons. Goals to be achieved is to know the development of cultural conservation of traditional art songs of Jav through the lessons of local content in elementary school and know the implications of the development of cultural conservation of traditional art songs of Java through the lessons of local content in the primary school in order to â€œnguri-uriâ€ Javanese culture. The results showed that the selection of local content selected by using the Java Tembang certain considerations, which are to memakasimalkan local potential and preserve Javanese culture-uri nguri Javanese culture. Learning the local content of Java Javanese song material having problems at school, among many classroom teachers who do not master the song Java so have difficulty in the delivery of the material and this led to a reluctance on the classroom teacher to deliver material Javanese songs. Implications of song learning in addition to preserving the song Java Java as one of the identity of the person to develop Java Java on the learnerâ€™s personality, because Java will be full of song, especially the charge of moral values and social values.